How to Think Bigger Than You Ever Thought You Could Think - Hansen, Mark (Ascent Audio, 2019)
When Mark Victor Hansen had to conquer his own setbacks in order to seize success, he discovered how to harness and leverage the power of the human mind and then to fuel it with enthusiasm and passion. His explorations took him beyond the normal confines of human thought, into the realms of imagination and possibility. Mark now travels the world in high demand as a keynote speaker, coaching people to wake up, to recognize their power to make a difference, and to re-create their reality by living their dreams. If you have ever experienced roadblocks and you have been looking for a way through, this program can be your road map. Mark's secrets, discoveries, and techniques will assist you in crushing your obstacles and helping to reveal true solutions. You'll learn powerful methods of creating passion, focus, and vision in your life.